The Application of The Sociodrama Method to Increase The Cooperative Ability of Children Age 5-6 Years - Royani, Ida; Astuti, Henny Puji (Jurusan PGPAUD FIP UNNES, 2020)
This study aims to explain the differences and improvement of the cooperation ability of children aged 5-6 years based on the application of the sociodrama method. The hypothesis in this study is that there are differences and improvements in the cooperation ability of children aged 5-6 years based on the application of the sociodrama method. This research uses quantitative research by using the One Group pretest-posttest design experimental method. The subjects in this research were children aged 5-6 years who became students in ABA 27 Kindergarten in Semarang, Gajahmungkur, Semarang City, group B, amounting to 30 children. The data collection technique used the cooperative ability scale, while the data analysis used the Paired Sample t-Test and Percentage Techniques. The results showed that there were differences and improvements in the cooperative ability of children aged 5-6 years based on the application of the sociodrama method. There are differences in the cooperative ability of children aged 5-6 years. The cooperative ability of children aged 5-6 years is higher after being given treatment. The increase in the cooperative ability with children aged 5-6 years based on the application of the sociodrama method was 38.03%.